Clinical characteristics and outcome of respiratory syncytial virus infection among adults hospitalized with influenza-like illness in France. (April 2017) - ; Seddik, K.; Lesieur, Z.; Bonmarin, I.; Loulergue, P.; Bodilis, H.; Servera-Miyalou, M.; Sadler, I.; Momcilovic, S.; Kanaan, R.; Coolent, N.; Tan Boun, K.; et al.
Abstract: Objectives: The aim of this study was to analyse characteristics and outcome of respiratory syncytial virus (RSV) infection in adults hospitalized with influenza-like illness (ILI). Methods: Patients hospitalized with ILI were included in this prospective, multicentre study carried out in six French hospitals during three consecutive influenza seasons (2012–2015). RSV and other respiratory viruses were detected by multiplex PCR in nasopharyngeal swabs. Risk factors for RSV infection were identified by backward stepwise logistic regression analysis. Results: A total of 1452 patients hospitalized with ILI were included, of whom 59% (861/1452) were >65 years and 83% (1211/1452) had underlying chronic illnesses. RSV was detected in 4% (59/1452), and influenza virus in 39% (566/1452). Risk factors for RSV infection were cancer (adjusted OR 2.1, 95% CI 1.1–4.1, p 0.04), and immunosuppressive treatment (adjusted OR 2.0, 95% CI 1.1–3.8, p 0.03). Patients with RSV had a median length of stay of 9 days (6–25), and 57% of them (30/53) had complications, including pneumonia (23/53, 44%) and respiratory failure (15/53, 28%). Fifteen per cent (8/53) were admitted to an intensive care unit, and the in-hospital mortality rate was 8% (4/53). Pneumonia was more likely to occur in patients with RSV than in patients with RSV-negative ILI (44% (23/53) versus 26% (362/1393), p 0.006) or with influenza virus infection (44% versus 28% (157/560), p 0.02). Conclusion: RSV is an infrequent cause of ILI during periods of influenza virus circulation but can cause severe complications in hospitalized adults. Risk factors for RSV detection in adults hospitalized with ILI include cancer and immunosuppressive treatment. Specific immunization and antiviral therapy might benefit patients at risk.